2013
DOI: 10.1534/g3.112.004994
|View full text |Cite
|
Sign up to set email alerts
|

Resequencing and Comparative Genomics of Stagonospora nodorum: Sectional Gene Absence and Effector Discovery

Abstract: Stagonospora nodorum is an important wheat (Triticum aestivum) pathogen in many parts of the world, causing major yield losses. It was the first species in the large fungal Dothideomycete class to be genome sequenced. The reference genome sequence (SN15) has been instrumental in the discovery of genes encoding necrotrophic effectors that induce disease symptoms in specific host genotypes. Here we present the genome sequence of two further S. nodorum strains (Sn4 and Sn79) that differ in their effector repertoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(72 citation statements)
references
References 69 publications
1
68
1
2
Order By: Relevance
“…This is consistent with studies in the US and Australia showing that many further effectors remain to be discovered (Abeysekara et al 2012;Crook et al 2012;Francki et al 2011;Friesen et al 2012;Oliver et al 2012;Syme et al 2013). In this study, we show that crude culture filtrates of a strain lacking expression of ToxA, SnTox1 and SnTox3 contain effector activity that induced reactions in 23 of the tested cultivars ( Table 2).…”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with studies in the US and Australia showing that many further effectors remain to be discovered (Abeysekara et al 2012;Crook et al 2012;Francki et al 2011;Friesen et al 2012;Oliver et al 2012;Syme et al 2013). In this study, we show that crude culture filtrates of a strain lacking expression of ToxA, SnTox1 and SnTox3 contain effector activity that induced reactions in 23 of the tested cultivars ( Table 2).…”
Section: Discussionsupporting
confidence: 92%
“…To this end, several general criteria based on existing knowledge about protein effectors from other fungal pathogens were established that ought to be fulfilled by candidate effector proteins ( cf. [116, 117]). Effectors are secreted, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…This suggests that this region is undergoing selective pressure which is significantly higher than other areas of the genome, particularly considering that the variations are not merely SNPs but larger variations of several hundred bases. A study conducted in Parastagonospora nodurum found a similar pattern, which was termed sectional gene absence (Syme et al, 2013).…”
Section: Pav Read Hits To Gene Annotationsmentioning
confidence: 88%
“…It appears that both LmUVI-1h and LmHDX are single-copy genes in L. maculans, which could have a deleterious effect on growth and infection success if absent. Interestingly, a cluster of genes, including a polyketide synthase, was also found to be lost in a comparison of isolates in Parastagonospora nodurum (Syme et al, 2013).…”
Section: Pav Read Hits To Gene Annotationsmentioning
confidence: 99%